Feasibility and oncological safety of sentinel node biopsy in breast cancer patients with a local recurrence. (October 2018) - Biglia, N.; Bounous, V.E.; Gallo, M.; Fuso, L.; Sgro, L.G.; Maggiorotto, F.; Ponzone, R.
Abstract: Objectives: To investigate the role and feasibility of sentinel lymph node biopsy (SLNB) in breast cancer patients with a local recurrence and no clinically positive axillary lymph nodes. Materials and Methods: A total of 71 patients underwent SLNB for breast cancer recurrence. At first surgery, they had received SLNB (46.5%), axillary lymph node dissection (ALND) (36.6%) or no axillary surgery (16.9%). Results: Lymphatic migration was successful in 53 out of 71 patients (74.6%) and was significantly higher in patients with previous SLNB or no axillary surgery than in those with previous ALND (87.9% vs. 53.8%; p = 0.009). Aberrant lymphatic migration pathways were observed in 7 patients (13.2%). The surgical SLNB was successfully performed in 51 patients (71.8%). In 46 patients (90.2%) the SLN was histologically negative, in 3 patients (5.9%) micrometastastatic and in 2 patients (3.9%) macrometastatic. The 2 patients with a macrometastates in SLN underwent ALND, In 4 out of the 18 patients with failure of tracer migration ALND, performed as surgeon's choice, did not find any metastatic node. After a median follow-up period of 39 months (range: 2–182 months), no axillary recurrence has been diagnosed. Conclusion: A SLNB in patients with locally recurrent breast cancer, no previous ALND and negative axillary lymph nodes is technically feasible and impacts on the ALND rate. In patients who at primary surgery received ALND, migration rate is significantly lower, aberrant migration is frequent and no clinically useful information has been obtained. Highlights: No agreement exists in sentinel lymph node biopsy for breast cancer recurrence. Lymphatic migration was successful in 74.6% of patients in our study. No axillary recurrences were observed after a median follow-up period of 39 months. Sentinel lymph node biopsy seems feasible and safe in breast cancer recurrence.